Famous Pitch Lake, La Brea, Trinidad - (:unkn) unknown (Photogelatine Engraving Co. Ltd., Ottawa, 2009)
Photo of employees at the La Brea Pitch Lake in Trinidad. No. 35.
Colour: Green, Brown, Blue and Yellow Hues; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Employees--Trinidad and Tobago; Asphalt industry--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--La Brea; Pitch Lake, The (La Brea)